Strategy Analysis of Retail Mix Implementation on Enhancing the Marketing Capabilities of MSMEs - Octaviani, Dewi; Astari, Yanisha Dwi (Jurnal EMT KITA, 2026)
This study aims to analyze how the implementation of the retail marketing mix enhances the marketing capabilities of micro, small, and medium-sized enterprises (MSMEs). In this study, marketing capabilities are operationally defined as MSMEs’ ability to implement marketing activities through retail mix elements, including product, price, place, promotion, service process, physical evidence, and marketing communication. This study was conducted at the Polbeng Business Expo Chapter II (2025) and focused on two MSMEs: Lapak TM Skuyy and Cemal Cemil JJ. A qualitative descriptive approach was employed, with data collected through interviews, observations, and documentation. Data analysis followed the Miles and Huberman qualitative analysis model. The findings show that product variety, affordable pricing, and strategic selling locations are the strongest indicators of marketing capability during the exhibition. However, promotion and marketing communication remain less optimized due to limited digital marketing skills and resources. Strengthening the integrated implementation of the retail marketing mix is essential to improving MSMEs’ marketing capabilities.